2013
DOI: 10.1115/1.4024285
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Novel Injectable Hydrogel Nucleus Pulposus Replacement in Restoring the Mechanical Properties of Cyclically Fatigued Porcine Intervertebral Discs

Abstract: Repeated flexion and extension of an intervertebral disc has been shown to affect the angular stiffness of spinal motion segments and is a barometer of the mechanical integrity of the disc. A degenerated disc that loses height causes higher levels of stress on the annulus and facet joints which may increase its level of degeneration; restoring disc height may therefore help to slow this degenerative cascade. Previous research has indicated that nucleus implants have the potential to improve the mechanical char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…This result indicated that these functionalized self-assembling peptides could be implanted into a disc via a minimally invasive injection, an approach which many studies have shown to be effective. 21,52,53 The results of this study indicated that the designed self-assembling peptides containing short BMP7 motifs have favorable feasibility for clinical applications in NP tissue engineering.…”
Section: Discussionmentioning
confidence: 93%
“…This result indicated that these functionalized self-assembling peptides could be implanted into a disc via a minimally invasive injection, an approach which many studies have shown to be effective. 21,52,53 The results of this study indicated that the designed self-assembling peptides containing short BMP7 motifs have favorable feasibility for clinical applications in NP tissue engineering.…”
Section: Discussionmentioning
confidence: 93%
“…Cyclic loading followed by hydrated recovery in human discs mimics this naturally occurring diurnal response [26]. In a previous study that used cyclic loading to evaluate a hydrogel implant in injured porcine discs, the implant demonstrated recovery of angular stiffness and disc height [30]. However, that study did not evaluate the effects of hydrated, unloaded recovery and thus could not evaluate the time-dependent mechanical response.…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, all measured biomechanical parameters (ROM, NZ length, and slow ramp, compressive, tensile and NZ stiffnesses) were restored to intact values upon hydrogel injection, while the Sham samples showed no improvements from their injured values. Although transannular discectomy has been found to measurably alter the compressive and tensile moduli, these parameters are often not restored using an NP replacement alone ( Balkovec et al , 2013 ; Malhotra et al , 2012 ; Smith et al , 2014 ). Therefore, the recovery of these parameters with the CMC 90 MC hydrogel in the current study was unique but must be interpreted with some qualification since the Sham group displayed no statistically significant effect of discectomy on the compressive and tensile moduli.…”
Section: Discussionmentioning
confidence: 99%
“…However, AF repair strategies alone may not fully restore IVD biomechanics. Recently developed NP replacements include hydrogels, because of their high water-content, tunable material properties, and ability to conform to the intradiscal space ( Balkovec et al , 2013 ; Gan et al , 2017 ; Pérez-San Vicente et al , 2017 ; Showalter et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%